2003
DOI: 10.1161/01.cir.0000053568.13058.67
|View full text |Cite
|
Sign up to set email alerts
|

Diesel Exhaust Particles in Lung Acutely Enhance Experimental Peripheral Thrombosis

Abstract: Background-Pollution by particulates has consistently been associated with increased cardiovascular morbidity and mortality, but a plausible biological basis for this association is lacking. Methods and Results-Diesel exhaust particles (DEPs) were instilled into the trachea of hamsters, and blood platelet activation, experimental thrombosis, and lung inflammation were studied. Doses of 5 to 500 g of DEPs per animal induced neutrophil influx into the bronchoalveolar lavage fluid with elevation of protein and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
250
2
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 257 publications
(271 citation statements)
references
References 42 publications
15
250
2
4
Order By: Relevance
“…Alternatively, the middle-aged population in epidemiological studies, though free of known cardiovascular disease, may have had some subclinical disease making them relatively more prone to inflammation than our young population. We also did not find a DE-associated increase in platelet numbers, consistent with prior study in a hamster model of DE particle exposure [20]. However, we did not directly test platelet activation, a more sensitive measure for which there is evidence in this hamster model.…”
Section: Discussionsupporting
confidence: 88%
“…Alternatively, the middle-aged population in epidemiological studies, though free of known cardiovascular disease, may have had some subclinical disease making them relatively more prone to inflammation than our young population. We also did not find a DE-associated increase in platelet numbers, consistent with prior study in a hamster model of DE particle exposure [20]. However, we did not directly test platelet activation, a more sensitive measure for which there is evidence in this hamster model.…”
Section: Discussionsupporting
confidence: 88%
“…Studies from several laboratories including our own (15, 19, 32, 48 -50) have demonstrated that a systemic inflammatory response is induced by exposure to ambient particulate matter exposure, supporting the hypothesis put forward by Seaton and colleagues (41). This systemic response is characterized by an increased release of PMN (49) and monocytes (19) from the bone marrow as well as elevated levels of circulating cytokines such as IL-6 and IL-1␤ (48), CRP (36), and procoagulation factors (15,32). Elevated levels of these proinflammatory effector cells and mediators in the circulation have been implicated in the pathogenesis of progression and destabilization Fig.…”
Section: Discussionsupporting
confidence: 72%
“…Recently several studies have shown that ultrafine particulate matter (UFP) can translocate from the lung into the peripheral blood (32)(33)(34); the biological downstream effects on circulating blood cells and blood vessels are still unclear. We speculate that translocated UFP may contribute to the decrease in circulating monocytes expressing CD11b after PM 10 exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, morphological study showed instilled 30 nm gold particles in capillaries within 30 minutes' postexposure (Berry et al, 1977) and inhaled ultrafine titanium dioxide particles at alveolar wall and in capillaries at 1 hour after the end of exposure (Geiser et al, 2005). UFPs in the blood circulation can directly or indirectly influence hemostasis or cardiovascular integrity and thus induce adverse cardiovascular endpoints more directly (Nemmar et al, 2002b(Nemmar et al, , 2003a(Nemmar et al, , 2003b. The exact pathway for this translocation, however, remains unclear.…”
Section: Introductionmentioning
confidence: 99%